2014
DOI: 10.1007/s00402-014-2039-z
|View full text |Cite
|
Sign up to set email alerts
|

Variability of tunnel positioning in ACL reconstruction

Abstract: This study demonstrates that a reasonable inter- and intra-observer variability in ACL tunnel positioning exists even among experienced surgeons. Although deviations of 2-3 mm may seem to be acceptable at first sight, a range of up to 18.3 mm indicates that outliers exist, which can cause graft failure. More reliable reconstruction techniques should be developed to reduce the variability in tunnel positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…There has been a recent increase of cadaveric studies that have identified radiographic landmarks of anatomic structures in various other orthopaedic surgical procedures, such as medial patellofemoral ligament, ACL, or LCL reconstructions, because the use of fluoroscopy has been shown to reduce the variability of tunnel positions. 12,17,19 Therefore, radiographic landmarks in LET procedures may similarly be useful in reducing the risk of tunnel misplacements, as well as in creating consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent increase of cadaveric studies that have identified radiographic landmarks of anatomic structures in various other orthopaedic surgical procedures, such as medial patellofemoral ligament, ACL, or LCL reconstructions, because the use of fluoroscopy has been shown to reduce the variability of tunnel positions. 12,17,19 Therefore, radiographic landmarks in LET procedures may similarly be useful in reducing the risk of tunnel misplacements, as well as in creating consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Shafizadeh [131] in a cadaveric set‐up analysed the variability of tunnel positioning. Thirteen experienced surgeons were asked to identify arthroscopically both the femoral and the tibial tunnels for two times.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have showed that CAS may improve the accuracy of anatomical tunnel orientation and position during ACL reconstructive surgery [15,29,38,51,57,82,92,103,109,111,139,143,144]. Shafizadeh [131] in a cadaveric set-up analysed the variability of tunnel positioning. Thirteen experienced surgeons were asked to identify arthroscopically both the femoral and the tibial tunnels for two times.…”
Section: Navigation and Tunnel Placementmentioning
confidence: 99%
“…Causes for revision include, but are not limited to, nonanatomic tunnel placement, inadequate notchplasty, improper tensioning, insufficient graft material, arthrofibrosis, skeletal malalignment, varus/valgus instability, surgical techniques, and the type of graft utilized [8,9]. Compared to the primary reconstruction, revision surgeries are more complex as the existing femoral and tibial tunnels complicate the creation of new tunnels [10,11]. Furthermore, the recommended graft type varies with each procedure; moreover, surgeons have to choose between a single-stage or a two-stage revision [12].…”
Section: Introductionmentioning
confidence: 99%